Hematopoietic stem cell transplantation recovers insulin deficiency in type 1 diabetes mellitus associated with IPEX syndrome. Issue 7 (24th July 2019) - Yamauchi, Takeru; Takasawa, Kei; Kamiya, Takahiro; Kirino, Shizuka; Gau, Maki; Inoue, Kento; Hoshino, Akihiro; Kashimada, Kenichi; Kanegane, Hirokazu; Morio, Tomohiro
Abstract: Immune dysregulation, polyendocrinopathy, enteropathy, and X‐linked (IPEX) syndrome is an autoimmune disorder caused by the dysfunction of FOXP3, which leads to regulatory T‐(Treg) cell dysfunction and subsequently autoimmunity including type 1 diabetes mellitus (T1D). Presently, allogeneic hematopoietic stem cell transplantation (HSCT) is a potential curative therapy for IPEX syndrome, but not for T1D. Generally, after complete loss of pancreatic β‐cells, HSCT cannot improve the prognosis of T1D. Here, we report the case of a 16‐year‐old adolescent with late‐onset of FOXP3 R347H mutation associated IPEX syndrome with T1D, where insulin dependency was ameliorated following HSCT. This patient with insulin‐dependent diabetes mellitus required insulin dosage of 1.28 U/kg/day for 1 month before HSCT. Although the results of glucose homeostasis before HSCT revealed impaired insulin secretion and low ΔC‐peptide immunoreactivity (CPR, 1.0 ng/mL), the patient withdrew insulin infusion and remained euglycemic at 15 months after HSCT, and had normal β‐cell function with improved ΔCPR (3.4 ng/mL) at 20 months after HSCT. The present case suggests that HSCT for T1D‐associated IPEX syndrome improves Treg deficiency and prevents elimination of β‐cells. We speculate that the period from the onset of T1D to HSCT could affect the therapeutic efficacy for T1D with IPEX, and early intervention with HSCT before or immediately after the onset of DM can rescue β‐cells and remit T1D completely. Our study elaborates not only the therapeutic strategy for T1D with IPEX, but also the pathogenic mechanism in general T1D.